BLOCKCHАIN TECHNOLOGY AS AN INNOVATIVE INSTRUMENT OF DIGITAL ECONOMY: TECHNOLOGY ESSENCE, WORLD EXPERIENCE AND IMPLEMENTATION PROBLEMS - Tetiana Momot; Daniele Tumietto; Roman Teslenko (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
The subject matter of the article is the substantiation of the problems and perspectives of the introduction of Distributed Ledger Technologies (DLT) / Blockchain in the public and private sectors as a modern digital economy instrument. The goal of the work is to substantiate the scientific and methodical principles of implementing the technologies of distributed DLT / Blockchain registers. The following tasks were solved in the article: the notion of Distributed Ledger Technologies (DLT) and Blockchain is defined; types of Distributed DLT Registries are presented in the form of a classification with a distinction of features and possibilities of application of each type; the general scheme of work is described and the specific features of the Blockchain technology are systematized;the features and directions of the use of intelligent contracts (smart contracts) based on the technology of blockchain are singled out;the international experience of government initiatives and pilot projects of the blockade technology application has been analyzed; the analysis of the domestic experience of practical application of Blockchain technologies in the public and private sectors and the perspective areas for the future application of technologies of the distributed DLT registries are identified; according to the international analytical agencies research results, the obstacles of the Blockchain technologies implementation in the public and private sectors are systematized. The following methods are used: abstract-logical analysis, theoretical generalization, system and statistical analysis. The following results were obtained. The concept of technologies of distributed DLT / Blockchain registries is disclosed. The availability of the system is based on open, private and federal DLTs. The specific features of DLT / Blockchain distributed registry technologies include centralization, involvement of a large number of participants to achieve consensus, use of cryptography and digital signatures, almost impossible to change chronological records, the convenience of tracking and verifying information, and the ability to program. The international experience of using Blockchain technology in countries such as the Great Britain, Georgia, Estonia, the USA, the United Arab Emirates, Italy has been researched. Examples of practical implementation of DLT / Blockchain registry technology in Ukraine are considered. The main obstacles to implementing distributed DLT / Blockchain registries in the public sector are regulatory restrictions and technology immaturity. The obstacles to the introduction of block technologies in the private sector are identified. Conclusions: It is proved that the distributed DLT registry technology has a significant potential for development for the future digital economy. Nevertheless, there are a number of barriers to their full use in the public and private sector, which requires further study by experts.